Microbubble-based fabrication of resilient porous ionogels for high-sensitivity pressure sensors - Ziwei Yang; Jingxiao Wang; Xiao Wan; Hongcheng Xu; Chuanyu Zhang; Xiaoke Lu; Weixuan Jing; Chuanfei Guo; Xueyong Wei (Microsystems & Nanoengineering)
Abstract High-sensitivity flexible pressure sensors have obtained extensive attention because of their expanding applications in e-skins and wearable medical devices for various disease diagnoses. As the representative candidate for these sensors, the iontronic microstructure has been widely proven to enhance sensation behaviors such as the sensitivity and limits of detection. However, the fast and tunable fabrication of ionic-porous sensing elastomers remains challenging because of the current template-dissolved or 3D printing methods. Here, we report a microbubble-based fabrication process that enables microporous and resilient-compliance ionogels for high-sensitivity pressure sensors. Periodic motion sliding results in a relative velocity between the imported airflow and the fluid solution, converts the airflow to microbubbles in the high-viscosity ionic fluid and promptly solidifies the fluid into a porous ionogel under ultraviolet exposure. The ultrahigh porosity of up to 95% endows the porous ionogel with superelasticity and a Young’s modulus near 7 kPa. Due to the superelastic compliance and iontronic electrical double-layer effect, the porous ionogel packaged into two electrodes endows the pressure sensor with high sensitivity (684.4 kPa−1) over an ultrabroad range (~1 MPa) and a high-pressure resolution of 0.46%. Furthermore, the pressure sensor successfully captures high-yield broad-range signals from the fingertip low-pressure pulses (<1 kPa) to foot high-pressure activities (>500 kPa), even the grasping force of soft machine hands via an array-scanning circuit during object recognition. This microbubble-based fabrication process for porous ionogels paves the way for designing wearable sensors or permeable electronics to monitor and diagnose various diseases.